Differing histopathology and prognosis in pulmonary adenocarcinoma at central and peripheral locations - Moon, Youngkyu (J Thorac Dis, 2016)
BACKGROUND: Pulmonary adenocarcinoma is largely peripheral in location but often does occur centrally. In the course of this study, clinicopathologic features of pulmonary adenocarcinoma, including the prognosis of early-stage disease, were assessed and compared by tumor location. METHODS: A retrospective chart review was conducted, examining 308 patients treated for pulmonary adenocarcinoma by curative resection. Clinicopathologic findings were analyzed, comparing central and peripheral primary locations. Recurrence-free survival (RFS) rates were determined for tumor subsets (central vs. peripheral). RESULTS: At all disease stages (N=308), 41 patients (13.3%) with central adenocarcinoma were documented. In central (vs. peripheral) adenocarcinoma, mean tumor size was larger (3.1 vs. 2.3 cm, P=0.014), nodal metastasis was more frequent (P=0.012), and the likelihood of advanced disease (stages II and III) was greater (P=0.007). Microscopically, central adenocarcinoma displayed more acinar (53.3% vs. 38.9%; P=0.006) and less lepidic (20.9% vs. 37.5%; P=0.001) growth. At stage I disease [N=329; central, 25 (10.5%)], group similarities were sustained. As with disease overall, central adenocarcinoma contained more acinar (51.8% vs. 37.1%; P=0.025) and fewer lepidic (26.2% vs. 44.1%; P=0.006) areas. Three-year RFS rates for central and peripheral adenocarcinoma at all disease stages were 63.2% and 82.5% (P=0.024), respectively, compared with 70.4% and 91.0% (P=0.023), respectively at stage I. Lepidic growth was identified as a statistically significant risk factor for early recurrence by multivariate analysis. CONCLUSIONS: Central pulmonary adenocarcinoma is generally detected at an advanced stage. In early (stage I) disease, the prognosis is comparatively worse for central adenocarcinoma, owing to significant micromorphologic differences in central and peripheral tumors.